Anticarcinogenic effect of alpha-lipoic acid and Jatropha gossypifolia leaves against cypermethrin-induced genotoxicity in rats - Opeyemi O. Faokunla; Oluseyi A. Akinloye; Regina N. Ugbaja; Abideen I. Adeogun (Journal of Medicinal Plants for Economic Development, 2018)
Background: Cypermethrin (Cyp), a synthetic pyrethroid developed for agricultural and public health applications, has become harmful to the environment and mammalian life owing to indiscriminate use.